Bi-allelic CCDC47 Variants Cause a Disorder Characterized by Woolly Hair, Liver Dysfunction, Dysmorphic Features, and Global Developmental Delay - Isikay, Sedat; Morimoto, Marie; Waller-Evans, Helen; Ammous, Zineb; Song, Xiaofei; Strauss, Kevin A.; Pehlivan, Davut; Gonzaga-Jauregui, Claudia; Puffenberger, Erik G.; Holst, Charles R.; Karaca, Ender; Brigatti, Karlla W.; et al. (CELL PRESS, 2018)
Ca2+ signaling is vital for various cellular processes including synaptic vesicle exocytosis, muscle contraction, regulation of secretion, gene transcription, and cellular proliferation. The endoplasmic reticulum (ER) is the largest intracellular Ca2+ store, and dysregulation of ER Ca2+ signaling and homeostasis contributes to the pathogenesis of various complex disorders and Mendelian disease traits. We describe four unrelated individuals with a complex multisystem disorder characterized by woolly hair, liver dysfunction, pruritus, dysmorphic features, hypotonia, and global developmental delay. Through whole-exome sequencing and family-based genomics, we identified bi-allelic variants in CCDC47 that encodes the Ca2+-binding ER transmembrane protein CCDC47. CCDC47, also known as calumin, has been shown to bind Ca2+ with low affinity and high capacity. In mice, loss of Ccdc47 leads to embryonic lethality, suggesting that Ccdc47 is essential for early development. Characterization of cells from individuals with predicted likely damaging alleles showed decreased CCDC47 mRNA expression and protein levels. In vitro cellular experiments showed decreased total ER Ca2+ storage, impaired Ca2+ signaling mediated by the IP3R Ca2+ release channel, and reduced ER Ca2+ refilling via store-operated Ca2+ entry. These results, together with the previously described role of CCDC47 in Ca2+ signaling and development, suggest that bi-allelic loss-of-function variants in CCDC47 underlie the pathogenesis of this multisystem disorder.
Keywords: UNDIAGNOSED DISEASES PROGRAM; CALCIUM-BINDING PROTEINS; ENDOPLASMIC-RETICULUM; CONSTITUTIVE ACTIVATION; TRANSMEMBRANE PROTEIN; ER STRESS; MUTATIONS; MUSCLE; IDENTIFICATION; CALRETICULIN